States of knowledge : the co-production of science and social order - Jasanoff, Sheila (International library of sociology., 2004)
The authors demonstrate that the idiom of co-production importantly extends the vocabulary of the traditional social sciences, offering fresh analytic perspectives on the nexus of science, power and culture.